Harmonia: Journal of Arts Research and Education - S. Suharto (editor) (Department of Drama, Dance nd Music, Faculty of Language, Univ. Negeri Se, 2021)
Harmonia merupakan jurnal riset dan pendidikan seni yang terakreditasi oleh Kemenristek/BRIN Number 148/M/KPT/2020 tanggal 3 Agustus 2020